Printing Spinoza : a descriptive bibliography of the works published in the seventeenth century - Ven, Jeroen van de (Library of the written word,, 2022)
"In Printing Spinoza Jeroen van de Ven systematically examines all seventeenth-century printed editions of Spinoza's writings, published between 1663 and 1694, as well as their variant 'issues'. In focus are Spinoza's 1663 adumbration of René Descartes's 'Principles of Philosophy' with his own 'Metaphysical Thoughts', the 'Theological-Political Treatise' (1670), and the posthumous writings (1677), including the famously-known 'Ethics'. Van de Ven's descriptive bibliography studies, contextualizes, and records all aspects of the publication history of Spinoza's writings from manuscript to print and assesses their immediate reception. It discusses the printed books' codicology, philology, typographical and textual relationships, illustration programmes, as well as their dissemination in early Enlightenment Europe, in view of the physical aspects of 1,246 extant copies and their provenance"--